The association between diabetes and head and neck squamous cell carcinoma: evidence from clinical cohort and bioinformatics analyses - He, Yurong; Chen, Jiaming; Han, Boxuan; Zhao, Yanming; Hou, Lizhen; Fang, Jugao; Lian, Meng (Frontiers in Genetics, 2025)
IntroductionDiabetes mellitus (DM) is a known risk factor for various cancers, but its relationship with head and neck squamous cell carcinoma (HNSCC) remains unclear. This study explores clinical and molecular links between DM and HNSCC through integrative analyses of patient data and bioinformatics.MethodsA retrospective cohort of 728 HNSCC patients was analyzed to assess sex-specific co-occurrence with DM. A simulation-based epidemiological model quantified associations based on observed clinical data and population incidence rates. Literature-based data mining was used to extract gene–disease associations for DM and HNSCC, followed by functional enrichment, pathway and network analyses of overlapping genes.ResultsThe simulation revealed a significant association between DM and HNSCC, stronger in males (Odds Ratio [OR] = 3.03, p = 6.28 × 10−50) than in females (OR = 2.18, p = 8.7 × 10−12). Data mining uncovered 3,489 overlapping genes (OR = 6.73, p < 4.95 × 10−319), including nine key genes (GPX4, NLRP3, CASP3, HOTAIR, SRC, IGF2BP2, APP, CYP2C19, and PVT1) tightly interconnected and functionally enriched in inflammation, metabolism, and neurological signaling pathways. Four genes—CYP2C19, NLRP3, PVT1, and APP—appear central to DM’s influence on HNSCC via the protein–protein interaction (PPI) network.ConclusionThese findings reveal a significant clinical and molecular connection between DM and HNSCC, especially in males, and highlight potential targets for future prevention and treatment strategies.